Case Report: Panic attack induced by albendazole in a post-PCI patient - Rijian Wang; Qiuyan Huang; Li Zhang (Frontiers in Psychiatry, 2026)
Background Albendazole is a widely used broad-spectrum anthelmintic whose recognized neuropsychiatric adverse effects are largely limited to encephalitis and demyelinating encephalopathy. Panic attack has not been previously reported as an adverse reaction to albendazole. Case presentation A 59-year-old Chinese man with recent percutaneous coronary intervention for coronary artery disease was prescribed albendazole (600 mg/day for 7 days) for an incidentally detected Clonorchis sinensis infection. Within hours of his first dose, he developed recurrent, unpredictable panic attacks characterized by palpitations, chest pain, dyspnea, derealization, fear of dying, and a sense of losing control. These episodes met DSM-5 diagnostic criteria for panic attack (11 of 13 core symptoms) and were graded as Grade 2 according to the Common Terminology Criteria for Adverse Events version 5.0. Extensive cardiac, pulmonary, and psychiatric workup excluded alternative causes. The panic attacks resolved following albendazole discontinuation and combination anxiolytic–antidepressant therapy. The Naranjo adverse drug reaction probability score was 8, indicating a probable causal relationship. Conclusions This case suggests that albendazole can probably induce acute panic attacks, expanding its neuropsychiatric adverse effect spectrum. In patients with heightened central nervous system vulnerability—such as those recovering from major cardiovascular procedures—the risk may be increased. For non-urgent anthelmintic indications in such patients, deferring treatment until clinical stabilization may be prudent.